Vibrating simulation and analysis teaching tool (VSATT): an interactive learning tool based on MATLAB simulink and GUI / Mohd Nor Azmi Ab Patar ... [et al.] - Ab Patar, Mohd Nor Azmi; Mahmud, Jamaluddin; Mat Jusoh, Mohammad Azzeim; Ismail, Mohd Shahrom; Abdul Wahab, Abdul Malek (College of Built Environment, 2023)
The use of a Graphical User Interface (GUI) as an interactive teaching tool has been increasingly popular in many areas of study.